Modelling of magnetorheological semi-active suspension system controlled by semi-active damping force estimator. (28th November 2011) - Bakar, Saiful Anuar Abu; Jamaluddin, Hishamuddin; Rahman, Roslan Abd.; Samin, Pakharuddin Mohd.; Masuda, Ryosuke; Hashimoto, Hiromu; Inaba, Takeshi
This paper presents the simulation study of magnetorheological semi-active suspension system controlled by a new proposed algorithm. The control algorithm named as Semi-Active Damping Force Estimator (SADE) is proposed to control the operations of the magnetorheological damper. The simulation of semi-active suspension system was done by considering actual dynamics behaviour of a custom-made magnetorheological damper, where its characteristic testing and modelling are described. The performance of magnetorheological semi-active car suspension system controlled by SADE in term of ride comfort is evaluated in comparison with normal suspension system. The performance of SADE semi-active suspension system is also compared with the skyhook-controlled semi-active suspension system performance. It is shown that magnetorheological semi-active suspension system controlled by SADE is able to improve vehicle?s ride comfort significantly compared to passive suspension system. The SADE-controlled semi-active suspension system performs more or less the same as skyhook-controlled semi-active suspension system.